Survey of Undergraduate Dentistry Students Awareness about Pulp and Periodontal Lesions in Fourteen Cities of Iran - Samineh Massah; Ehsan Rafiei; Parisa Ranjbarian (Isfahan University of Medical Sciences, 2022)
Inflammation and infection can spread from the dental pulp to the periodontal tissue and from the periodontium to the pulp. Given the challenging nature of diagnosing endodontic-periodontal lesions and the importance of appropriate treatment to improve dental prognosis, this study was performed to evaluate the knowledge of dental students about the diagnosis of pulp and periodontal lesions.Materials & Methods:In this analytical observational study, a questionnaire was designed to assess knowledge on pulp and periapical lesions in three areas of theoretical knowledge, knowledge in diagnosis and knowledge in treatment in the second semester of the academic year 2021 and filled out by 400 dental students representing 15 cities of Iran. Data analysis was performed by Friedman, Wilcoxon and Mann-Whitney tests (α = 0.05).Results:Percentage of correct answer of dental students to the questions related to theoretical knowledge 65.70 ± 18.39, percentage of correct answer to the questions of students' diagnostic knowledge 50.75 ± 33.28, percentage of correct answer to the questions of treatment knowledge 52.13 ± 23.93 and the percentage of correct answers to the questions of knowledge in total was 56.68 ± 16.35, which is statistically significant in terms of knowledge in the three areas studied (p value < 0.001).Conclusion:In the present study, it was shown that the highest level of appropriate knowledge in students is in the field of theoretical knowledge of endodontic-periodontal lesions and the least level of appropriate knowledge was in the field of diagnosis of these diseases. The overall knowledge of students in this study about endodontic-periodontal lesions was shown to be moderate